ANALYSIS OF PAREMIAS REPRESENTING THE RELATIONSHIP BETWEEN MEN AND WOMEN IN THE UZBEK LANGUAGE - Madaminova, Gulbahor (Журнал иностранных языков и лингвистики, 2021)
Semantics address meaning at the levels of words, phrases, sentences, proverbs or larger units of discourse. The versatility of the semantic sphere of several paremias is a bit of a challenge; therefore, their belonging to this or that group has been determined semantically rather than lexically